Is the management of acute confusional syndrome secondary to covid-19 pneumonia different from the management of confusional syndrome secondary to other causes? - A. Llimona González; M. Calls Samora; D. García Hernández; S. Oller Canet (European Psychiatry, 2022)
Introduction Acute Confusional Syndrome (ACS) is the most common neuropsychiatric complication in COVID-19 infection. Its management is still a challenge because the data and recommendations based on the evidence are limited.